1575. Clinical Validation of a Novel ELISpot-based in vitro Diagnostic Assay to Monitor CMV-Specific Cell-Mediated Immunity in SOT and HSCT Immunocompromised Patients. (26th November 2018) - Banas, Bernhard; Steubl, Dominik; Renders, Lutz; Chittka, Dominik; Banas, Miriam; Wekerle, Thomas; Koch, Martina; Witzke, Oliver; Lindemann, Monika; Muehlfeld, Anja; Sommerer, Claudia; Habicht, Antja; et al.
Abstract: Background: Impaired cytomegalovirus (CMV)-specific cell-mediated immunity (CMV-CMI) is a major cause of uncontrolled CMV reactivation and associated complications in both solid-organ transplantation (SOT) and hematopoietic stem cell transplantation (HSCT). Reliably assessing CMV-CMI is desirable to individually adjust antiviral and immunosuppressive therapy. We demonstrate here the suitability of a novel IFN-γ ELISpot assay (T-Track ® CMV), based on the stimulation of PBMC with pp65 and IE-1 CMV proteins, to monitor CMV-CMI in SOT and HSCT patients. Methods: Two independent prospective, longitudinal, observational, multicenter studies were conducted: in 86 intermediate-risk (D−/R+, D+/R+) renal transplant recipients (completed), and in 175 intermediate- or high-risk (D+/R+, D+/R−, D−/R+) HSCT recipients (ongoing). In both studies, patients underwent pre-emptive antiviral therapy. CMV-CMI, CMV load and clinical complications were monitored over ~6 months post-transplantation. Results: In the kidney transplantation setting, 95% and 88–92% of IFN-γ ELISpot test results were positive pre- and post-transplantation, respectively. CMV-specific response was reduced following immunosuppressive therapy and increased in patients with graft rejection, indicating the ability of the assay to monitor the patients' immunosuppressive state. Interestingly, median pp65-specific response was 9-fold higher in patients with self-clearing viral load compared with antivirally-treated patients prior to first detection of CMV (MWU; P < 0.001), suggesting that reactivity to pp65 is a potential immunocompetence marker. In HSCT patients, interim data analysis indicates that pp65-specific CMI measured after resolution of a primary CMV reactivation (requiring antiviral treatment) is a fair predictor of occurrence of recurrent CMV reactivation. Out of 71 patients (25 D+/R+, 3 D+/R−, 43 D−/R+) who experienced a primary CMV reactivation, 27 encountered a recurrent CMV reactivation. Interestingly, 39/44 (89%) patients free of recurrent reactivation had a positive pp65-specific test result following primary CMV reactivation. Conclusion: Altogether, this novel IFN-γ ELISpot assay is a highly sensitive immune-monitoring tool with a potential use for the risk assessment of CMV-related clinical complications after SOT and HSCT. Disclosures: All authors, Lophius Biosciences: Investigator, Research support.